2019
DOI: 10.1101/843680
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Loss of IKK subunits limits NF-κB signaling in reovirus infected cells

Abstract: 18

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
1
1
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(12 citation statements)
references
References 47 publications
(57 reference statements)
1
10
1
Order By: Relevance
“…2). Thus, σ3 inhibits NF-κB via a different mechanism than what has been described previously (13). We found that σ3 inhibits the expression of some but not all NF-κB target genes (Fig.…”
Section: Discussionsupporting
confidence: 55%
See 3 more Smart Citations
“…2). Thus, σ3 inhibits NF-κB via a different mechanism than what has been described previously (13). We found that σ3 inhibits the expression of some but not all NF-κB target genes (Fig.…”
Section: Discussionsupporting
confidence: 55%
“…Sensing of reovirus genomic RNA by RLRs leads to the activation of IRF3 and NF-κB, which lead to the production of interferon (IFN) and other inflammatory cytokines (9)(10)(11)(12). (13). Consistent with this, the genetic absence of either IRF3 or NF-κB exacerbates reovirus disease in a newborn mouse model (14,15).…”
Section: Introductionmentioning
confidence: 86%
See 2 more Smart Citations
“…Antiviral cytokines are also under control of nuclear factor kappa B (NF-kB), a family of transcription factors. It has been suggested that NF-kB is rendered inactive because virus infection results in reduced levels of inhibitor of kappa B kinase (IKK) complex, which is needed for NF-kB function ( 35 ). The canonical complex of IKK is composed of IKKα/IKKβ/IKKγ.…”
Section: Resultsmentioning
confidence: 99%